Analisis Implementasi Distribusi di PT. Mahardika Jujur Mandiri (MJM) Bandung - Budi Prasetiyo; Rizky Alamsyah (Universitas Kristen Indonesia Toraja, 2025)
The research entitled “Analysis of Distribution Implementation at PT Mahardika Jujur Mandiri (MJM) Bandung” is intended to provide solutions with the aim of improving performance and management at PT Mahardika Jujur Mandiri (MJM). This research focuses on improving literacy in the stock inventory system, ordering goods and the flow of distribution of goods from PT. Mahardika Jujur Mandiri (MJM) to retail / stores. This community service program was held at PT Mahardika Jujur Mandiri (MJM) Bandung on Jl. Rancakendal Luhur No. 8, Desa Ciburial, Kecamatan Cimenyan, Kabupaten Bandung. The research approach is educative and interactive. This research began on September 16, 2023. This approach is carried out by the method of discussion, field studies, and cooperation between individuals. This service is in line with the company's vision and mission, namely to make a leading trading group in West Java and dedicated to serving reliably and premiumly. The results of community service are in line with the needs of the company, and the results of community service can be accepted by the company. Although at first there were problems such as the preparation of goods that were still not organized and separated, it is hoped that the results of this community service will be the first step for the company to improve the warehouse system and its own human resources.